1980
DOI: 10.1039/f19807601311
|View full text |Cite
|
Sign up to set email alerts
|

Superacidity of modified γ-Al2O3. Structure of active site and catalytic activity

Abstract: Fhysico-chemical and catalytic properties of alumina exposed to PZOS, AlC13, CH,AICl2, PC13, PCls and HzP03F vapours have been studied. Catalysts obtained by treatment with PzOS, AlC13 and CH3AlC12 vapours are marked by very high acidity and catalytic activity which classify them among the solid superacids. From an i.r.investigation of ammonia adsorption coupled with e.s.r. measurements of perylene adsorption it has been demonstrated that solid superacids exhibit Lewis-type acid behaviour. The structure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…The simultaneous removal of chemisorbed HCl (spectrum 3 in Figure b) leaves an extensively chlorinated surface, as verified by complementary FT‐IR experiments (Supporting Information, Figure S1 a). Although the formation of a crystalline AlCl 3 phase was excluded by x‐ray powder diffraction (XRPD) measurements (Supporting Information, Figure S1 b), the chlorination may easily involve also subsurface layers and has a key role in the catalysis, both enhancing the Al 3+ Lewis acidity and positively affecting the Ti 3+ center activity . The final amount of Ti present in the catalyst (approximately 2 wt %, as determined by ICP analysis) is in good agreement with that expected by considering the involvement of all the surface OH groups (approximately 4 OH/nm 2 ).…”
Section: Figuresupporting
confidence: 72%
“…The simultaneous removal of chemisorbed HCl (spectrum 3 in Figure b) leaves an extensively chlorinated surface, as verified by complementary FT‐IR experiments (Supporting Information, Figure S1 a). Although the formation of a crystalline AlCl 3 phase was excluded by x‐ray powder diffraction (XRPD) measurements (Supporting Information, Figure S1 b), the chlorination may easily involve also subsurface layers and has a key role in the catalysis, both enhancing the Al 3+ Lewis acidity and positively affecting the Ti 3+ center activity . The final amount of Ti present in the catalyst (approximately 2 wt %, as determined by ICP analysis) is in good agreement with that expected by considering the involvement of all the surface OH groups (approximately 4 OH/nm 2 ).…”
Section: Figuresupporting
confidence: 72%
“…Thel ocal environment of the EPR active Ti 3+ ions is revealed by hyperfine sublevel correlation (HYSCORE) experiments at Qband frequency (34.3 GHz), which allow detecting the NMR transitions of magnetically active nuclei in the vicinity of the paramagnetic center. Atypical HYSCORE spectrum is shown in Figure 1c.The spectrum is dominated by an extended ridge signal centered at 13.8 MHz ( 27 Al Larmor frequency at this field) with am aximum extension of approximately 21 MHz, arising from the hyperfine interaction of the unpaired electron localized on the Ti 3+ with 27 Al nuclei of the alumina support. The 27 Al signal is consistent with ah yperfine interaction dominated by the isotropic Fermi contact contribution (a iso ), [32] ranging between 5a nd 20 MHz (Table S1).…”
mentioning
confidence: 93%
“…Atypical HYSCORE spectrum is shown in Figure 1c.The spectrum is dominated by an extended ridge signal centered at 13.8 MHz ( 27 Al Larmor frequency at this field) with am aximum extension of approximately 21 MHz, arising from the hyperfine interaction of the unpaired electron localized on the Ti 3+ with 27 Al nuclei of the alumina support. The 27 Al signal is consistent with ah yperfine interaction dominated by the isotropic Fermi contact contribution (a iso ), [32] ranging between 5a nd 20 MHz (Table S1). Such isotropic couplings provide au nique and direct confirmation for the presence of Ti 3+ ÀClÀAl linkages, corresponding to aspin density transfer in the 3sAl orbital in the range of 0.15-0.60 %, which is significantly larger than that observed for other systems involving M(3d 1 ) À L À Al linkages.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Although the role of Lewis acid sites during cracking reactions of acyclic paraffins is still unclear, there is considerable evidence that these sites are active during skeletal isomerization of both acyclic and cyclic paraffins. It is suggested that isomerization of methylcyclopentane to cyclohexane occurs via hydride ion extraction at Lewis acid sites on various solid superacid catalysts (Krzywicki and Marczewski, 1980;Hattori et al, 1981;Takahashi and Hideshi, 1981). This would also seem plausible for this reaction on HY, so that while reactions involving ring opening and cracking occur mainly on Bronsted sites via protonation of the ring, skeletal isomerization may occur mainly on Lewis acid sites.…”
Section: Skeletal Isomerizationmentioning
confidence: 99%